Level Of Skilling Skills Speed Classic Categories Nature Living Students Dehasen University Bengkulu - W. Rahayu; Suwarni Suwarni; Martiani Martiani (Sinar Sport Journal, 2021)
The purpose of this study was to determine the level of rock climbing ability in the speed classic category of wall climbing. The subjects of this research are students who love nature at the Dehasen Bengkulu University. which amounted to 20 students where the fastest time for male students was 11.43 seconds while the fastest time for girls was 14.14 seconds. rock climbing ability in the speed classic category. Dehasen Bengkulu University students, as many as 2 students (10%) had a "very good" category, 5 students (25%) had a "good" category, 8 students (40%) had a "fairly good" category. , 3 students (15%) have a "less" category, and 2 students (10%) have a "very poor" category. The highest frequency was in the "good enough" category, namely 8 students (40%) so it can be concluded that the level of rock climbing ability in the speed classic category of students at the University of Dehasen Bengkulu using the climbing speed test was "good enough". The frequency of exercise which is approximately twice a week is still not enough to improve rock climbing ability in the speed classic category. This is because in training, of course there are programs from trainers that emphasize more on techniques and strategies in climbing without looking at students' abilities.